Microbial solutions for plastic pollutants: Caprolactam, Polyvinyl alcohol, and surgical face masks - Ashvini Vetal; Kiran Patil; Apurva Pawar; Gayatri Atre; Aparna Gunjal; Meghmala Waghmode (Ruhuna Journal of Science)
Caprolactam and polyvinyl alcohol (PVA) are plastic pollutants that in excess concentrations affect the environment adversely. The purpose of this study was to identify the microorganisms with the potential to break down biodegradable polyvinyl alcohol synthetic plastic polymer caprolactam, and face masks. Caprolactam and PVA-degrading bacteria were isolated from the soil. The identification of the isolate was done using morphological, biochemical and 16S rRNA sequencing and identified as Pseudomonas aeruginosa. Colorimetric and reverse-phase high-performance liquid chromatography analysis revealed the degradation of 61 and 96 % caprolactam (1%) and PVA (0.1%) respectively by the isolate. The degradative product of caprolactam and polyvinyl alcohol was identified as adipic acid and fumaric acid based on the mass spectroscopic analysis. Field emission scanning electron microscopy of the control and bacterial-treated face mask was carried out to check the degradation potential of the strain. Microbial face mask degradation showed 97.89 % reduction in the diameter of fibers, which proved the potential use of Pseudomonas aeruginosa in the remediation of bioplastic, synthetic and microplastic polluted areas.